Technopreneurship Enhancing Student MSMEs Competitive Edge via Digital Marketing - Ismiyanti, Yulina; Prajanti, Sucihatiningsih Dian Wisika; Utomo, Cahyo Budi; Handoyo, Eko; Banowati, Eva; Kusmaryono, Imam; Huda, Muhammad Nur (Pandawan, 2026)
This research aims to analyze the role of technopreneurship in increasing the competitive advantage of student MSMEs in Semarang City through digital marketing capability. This study uses a quantitative approach. The sampling technique in this research is a quota random sampling technique. This technique is used because the grouping of MSMEs is united into one group, namely the student MSME group in Semarang City which is technology oriented. The number of samples in this research was 120 student MSME actors in Semarang City. The analytical method used in this research is Structural Equation Modeling (SEM) analysis with the help of the SmartPLS program. The research results show that digital marketing capability and innovation capability directly have a positive and significant influence on the competitive advantage of student MSMEs in Semarang City. Technopreneurship has a significant effect on competitive advantage. Indirectly, technopreneurship has a significant effect on competitive advantage through digital marketing capability. However, indirectly, innovation capability has no significant effect on competitive advantage through digital marketing capability. The implication of this research is that student MSMEs that are run by students tend to be more adaptive to technological developments, so that a technopreneurship approach will be very helpful in increasing the competitive advantage of student MSMEs.